Child trafficking in the EU: policing and protecting Europe's most vulnerable - Fussey, Pete (Routledge studies in crime and society, 2017)
Introduction -- Trafficking : perspectives and provocations -- Control and the limits of criminalisation -- Borderless people in bordered world : the Romani and transnational marginalisation -- Collaboration, cooperation and conflict : policing the trafficking of roma children -- Return to sender : repatriation and rehabilitation -- Conclusions -- Index